Retranslation in popular culture: a multimodal extension of taboo love. (2nd January 2020) - Jiang, Mengying
ABSTRACT: Whilst research on retranslation focuses primarily on literary and interlingual translation, this article investigates how gay audiences' intralingual and intersemiotic retranslation can facilitate a participatory culture for gender minorities in China. It draws insights from fandom studies, hermeneutics of translation and Mikhail Bakhtin's carnival notion to conceptualise retranslation in fandom. It first discusses the 'socialist sisterhood' as dubbed by viewers in the most Googled Chinese TV show of 2018, The Story of Yanxi Palace and then compares the sisterhood narrative and the female gay fans' alternative lesbian-themed slash fictions, fakesubs, pictures and videos as intersemiotic retranslations. Such a 'transmedial translation series' bridges the classic and the modern, the local and the foreign, the mainstream and the marginal, and re-inscribes them in different media. Ultimately, it facilitates the formation and dissemination of a subculture that has mesmerised a specific community of young Chinese, but is not recognised by the official culture. This article argues that rather than traversing literary, cultural and historical boundaries, retranslation can also cross normative and non-normative sexual divides and provide free and interactive sites for collectives to combat conformity, break taboos and conventions, and make themselves more visible in today's internet-mediated society.